Fostering Students To Become Hafidz Qur’an In Griya Tahfidz Nurul Qur’an Tlogoanyar Lamongan - Karimatul Inayah; Nicky Estu Putu Muchtar (Shof Literacy Community, 2024)
The Qur'an is the holy book of the noble Muslims, reading it will get a reward especially those who memorize it, many memorize the Qur'an but there must be someone who guides, fosters. The purpose of this service activity is to foster students carried out by the ustadzah to make their students become hafidz quran at Griya Tahfidz Nurul Quran Tlogoanyar Lamongan district which includes planning, implementation, and evaluation. The method used is using a qualitative approach with a case study type of research. The final result of this activity is to show that the development of Nurul Quran students in Tlogoanyar Lamongan to become memorizers of the Koran by fostering the enthusiasm of the students to memorize, study, study the Koran, has proven to have been done very well so as to make the students as hafidzul qur'an, in addition to having good memorization quality, but also qur'ani morals.